Effects of Decapitation, Water-Deficit Stress, and Pot Size on Morpho-Anatomy and Physiology of Pterocarpus indicus - Hernandez, Jonathan Ogayon; Combalicer, Marilyn Sabalvaro; Umali, Arthur Glenn Agojo; Maldia, Lerma San Jose (Department of Forestry, Faculty of Agriculture, University of Lampung, 2024)
The interacting effects of stem decapitation, water-deficit stress, and pot size on the growth, morpho-anatomical, and physiological traits of Pterocarpus indicus seedlings were analyzed in this study. Changes in root collar diameter (RCD), biomass allocation, number of leaflets (NL), mean leaf area, guard cell size, stomatal aperture size, phloem cap fiber (PCF) thickness, xylem vessel density (XVD), relative leaf water content (RWC), stomatal conductance (gsw), transpiration rate (E), fluorescence quantum yield, transpiration (E), photosynthesis (PN), and electron transport rate (ETR) of decapitated and undecapitated P. indicus seedlings in different pot sizes (small, medium, large) and watering regimes (every 2, 7, and 14 days) were analyzed. The decapitation × water-deficit stress × and pot size interaction did not affect growth and morpho-anatomical variables, but they did on most of the physiological traits. Decapitated seedlings watered every 14 days and planted in medium or large pots have lower gsw, PN, E, and RWC. While the RCD of large-potted and water-stressed (every 14 days) seedlings decreased, allocations to stem and fine roots increased. Moreover, the NL and PCF significantly decreased, while the ETR and XVD significantly increased in decapitated and water-stressed seedlings. Overall, the decapitation-watering interaction caused significant stress to P. indicus seedlings. Keywords: biomass allocations, decapitation, drought stress, multiple stress, xylem vessel density